Dalla linguistica alla psichiatria: Tell me where Phantasy is bred - Rocchi, Ilaria (Il sogno della farfalla, 2022)
The aim of this paper is to investigate the meaning of the word Phantasy in the Early modern English of the 16th century. During that time, this term encompassed contrasting meanings such as imagination, hallucination and desire. In the attempt to understand the hidden thread connecting these concepts, the author carries out an etymological and linguistic journey. In particular, the use of the word phantasy is analyzed in the Shakespearean play A midsummer night’s dream. Drawing from the paper Some notes on paranoid and schizophrenic delusional perception and the human birth theory by Massimo Fagioli, this paper proposes a line of research to investigate the root of this word, underlying the essential role of psychiatry to deepen our understanding of language and its unconscious images and thoughts.